Investigation and reduction of internal stress in nickel sulfamate electrolyte electroforming process through temperature and electrolyte composition variation - Tay, Yi Li (2019)
Internal stress caused by electrodeposition using previously found optimum conditions were investigated and reduced. This project aims to achieve internal stress that is within the acceptable range of -8 kgf/mm2 to 0 kgf/mm2. Internal stress values induced by using optimum conditions were found to be tensile in nature and much higher than the acceptable range, at about 84.584 kgf/mm2. Rectification included the lowering of plating bath temperature from 55°C to 35°C, which dropped the internal stress value by more than half. Nickel (II) Bromide was also found to possibly be a better alternative to Nickel (II) Chloride as the source for halide ions. Overall, internal stress was reduced by about 9 times the initial amount to 9.053 kgf/mm2, but is still not within acceptable range. As this is an ongoing project, further investigations and researches will be required to prove Nickel (II) Bromide as an alternative and to reduce internal stress down to the acceptable range.